ДЕРЖАВНА ПОЛІТИКА ЩОДО ОХОРОНИ І БЕЗПЕКИ ПРАЦІ В УКРАЇНІ - Hayuk, Maksym (Zhytomyr Ivan Franko State University, 2024)
The article looks at how Ukraine treats workers' health and safety. Occupational health and safety is a system of measures and means that are used by legal entities and people to make sure that working conditions are good enough to prevent threats to an employee's life and health while he is doing his job. The essence and principles of state policy in the field of occupational safety and health have been explained. These principles include the importance of protecting the life and health of employees, the responsibility of the employer for creating safe and healthy working conditions, the need to keep production, technologies, and products safe and harmless, and the need to help enterprises create safe and harmless working conditions.  We need to solve occupational safety problems using programs from different parts of the country and around the world. We should also consider other things like science and technology, protecting the environment, protecting workers, and paying people who get hurt at work or get sick at work. Creating safety rules for all businesses, no matter who owns them or what they do. Making sure workers are safe and healthy by changing how they work, considering their health and mental state. The government can help pay for safety measures, but only if it doesn't go against the rules. It is said that occupational safety and health have a big impact on modern economic processes. Economic importance is measured by how well workers work, how much money they make from working, and how much they pay for injuries or illnesses that affect their health and safety.